Clinical implications of systemic lupus erythematosus without and with antiphospholipid syndrome in peri- and postmenopausal age - Grygiel-Górniak, Bogna; Limphaibool, Nattakarn; Puszczewicz, Mariusz (Menopause Review/Przegląd Menopauzalny, 2018)
Antiphospholipid syndrome (APS) in patients with systemic lupus erythematosus (SLE) displays a severe disease sub-phenotype with vascular manifestations ranging from peripheral thrombosis to neurologic and ophthalmic symptoms. The prevalence of morbidities including thrombosis, renal lesions, and cognitive impairment contributes to a higher risk of organ damage and a reduced quality of life in patients. In addition to the clinical heterogeneity, the diagnostic challenge is heightened in elderly patients as APS-related SLE is primarily diagnosed in young females. Many patients reach menopause due to the clinical association of premature menopause and improvements in diagnostic and therapeutic strategies in recent years. Although obstetric morbidity is not a concerning feature of the disease within this age group, a number of manifestations which may contribute to a decreased quality of life are present and must therefore not be disregarded. An improved prognosis derives from successful therapeutic regimens with minimal adverse effects in individual patients. The multifaceted management involves patient evaluation and risk stratification, followed by thromboprophylaxis efforts through the correction of modifiable risk factors, lifestyle recommendations, and pharmacological therapy. This review highlights the role of estradiol in the disease pathogenesis as well as the clinical complications and management of APS-related SLE in perimenopausal and postmenopausal patients.